A Photovoice Study on the Lived Experiences of Youth and Mothers of Incarcerated Fathers and Husbands, Highlighting the Relevance of Abolitionist Social Work Practice - Elizabeth K. Allen; Jason Ostrander; Kate Kelly (Social Sciences, 2025)
This community-based participatory research (CBPR) study explored, using a Photovoice methodology, the lived expeiences of northeastern Black and/or African American youth and mothers who were currently experiencing the incarceration of their fathers and husbands. Grounded in critical theories of dual consciousness and comparative conflict, the findings provide valuable insights into how this population navigates the intersections of family, school, and community within the context of the criminal legal system, and, in the process, underscore the relevance of Abolitionist practice in capturing their theoretically lived experiences. Participants documented through photography and narrative reflections the multifaceted impacts of incarceration on fathers and husbands, including disrupted family dynamics, social stigma, and barriers to community resources. A focus group with the mothers of these youth highlighted the profound impact of incarceration on their family structure, revealing significant emotional burdens for caregivers as well as personal changes to parenting styles as a result of this project. A central theme that emerged was the development of a “double” or “dual consciousness”—an ability to see humanity and injustice in their circumstances, fueling a desire for systemic change. Overall, this CBPR project amplifies the voices of marginalized youth and mothers, illuminating how the criminal legal system perpetuates cycles of trauma, stigma, and disempowerment. The implications call for a radical reimagining of the role of social work in creating more equitable, restorative, and healing-centered communities, including an immediate embrace of Abolitionist practice concepts and interventions.